Pengaruh Gaya Kepemimpina dan Kompensasi Terhadap Kinerja Guru PNS di SMP Negri 3 Padalarang - Muhammad Fiqih; Ahmad Drajat Aji Sujai (Cakrawala Repositori IMWI, 2023)
This study focuses on knowing and analyzing whether or not there is an influence between the influence of leadership (X1), compensation (X2) on teacher performance (Y) at SMPN 3 Padalarangg. The method used by the author is a descriptive and verification research method. Respondents were 33 PNS teachers at SMPN 3 Padalarang. The research data obtained was processed and analyzed quantitatively. As well as further processing with tools in the form of theoretical foundations studied previously so as to clarify the description of the object under study and then conclusions are drawn from these results. After the authors obtained the data, it was then processed and analyzed using qualitative and quantitative analysis. The results showed that leadership style (X1) and compensation (X2) had an effect on performance (Y).